ESSONODONTHERIUM GERVAISI ES UN SINONIMODE MEGATHERIUM AMERICANUM CUVIER (XENARTHRA, MAMMALIA) (Ameghiniana, 2013)
The giant ground sloth Essonodontherium geroaisi (H. Gervais and F. Ameghino), based on a single skull and mandible, is shown to be a teratological specímen of Megatherium americanum. Ontogenetic fusion of the first two teeth in the mandible and the second and third .teeth in the maxilla accounts for the apparent reduction in tooth number. The other differences from M. americanum, can be attributed to thís dental anornalv. There is no evidence to support Ameghíno's contentíon that E. geroaisi is either more highly evolved or of younger geological age than M. americanum.